INDONESIAN NATIONAL HEALTH INSURANCE (JKN) AND MATERNAL CARE UTILIZATION - Sambodo, Novat Pugo; Wahyuni, Heni; Sekaringsih, Riswanti Budi (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.14.NO.05.TAHUN.2025, 2025)
This study uses Indonesian Family Life Survey data to estimate the association of health insurance under Jaminan Kesehatan Nasional (National Health Insurance) with maternal health care utilization. The data for this research is from the IFLS 5. The estimation uses a negative binomial regression. The results of the prenatal care estimation show that the explanatory variables have the expected signs. Key variables in the analysis, which are any health insurance and national universal health coverage insurance ownership, positively and significantly associated with  maternal healthcare utilization. Having any insurance and national universal health coverage increases a mother's expected prenatal care usage. The results highlight the importance of having any or national universal health coverage insurance for a mother who seeks prenatal care services when she gets pregnant, thus contributing to healthier pregnancy outcomes. There has been limited research undertaken in Indonesia relating to the impact of health insurance on the use of maternal health care services, especially that explores the health insurance and the utilization of maternal health care services using an appropriate method.